Integrated marketing communication : creative strategy from idea to implementation - Blakeman, Robyn, 1958- (Lanham: Rowman and Littlefield, 2024)
"Now in its fourth edition, this comprehensive text offers a classroom-tested, step-by-step approach to the creative processes and strategies for effective integrated marketing communication (IMC)"--
Revised edition of the author's Integrated marketing communication, [2018]
Includes bibliographical references and index.
Keywords: Communication in marketing